The Strategic Marketing of Community-Based Sustainable Tourism with a Three-Phase Framework - Keenandya Zata Amani; Rajiv Mangruwa (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Community-based sustainable tourism emphasizes local participation and environmental preservation, yet effective marketing strategies remain underexplored, particularly for niche destinations like cave-based tourism. This study aims to analyze the marketing strategies of Buniayu Cave in Kertaangsana Village, Sukabumi Regency, identify factors influencing their effectiveness, and propose a model for sustainable tourism development. A qualitative descriptive approach was employed, using in-depth interviews, participant observation, and documentation, with data analyzed through the Political, Economic, Social, and Technological framework. Findings reveal that community involvement in promotional content creation enhances authenticity and increases local income by 15–20%, while value-based pricing supports economic empowerment. However, the absence of formal institutional partnerships and reliance on manual reservation systems limit promotional reach and operational efficiency. The proposed three-phase model, foundation, market growth, and industry outcomes, integrates these factors to drive customer engagement and sustainability, aligning with Sustainable Development Goals for decent work, sustainable communities, and responsible consumption. In conclusion, formal partnerships, professional training, and digital system upgrades are essential to optimize Buniayu Cave’s marketing, offering a scalable framework for community-based cave tourism that balances economic growth with environmental and cultural preservation.